Investigating the Impact of Parental Divorce on Emotional Development in Early Adolescents: Insights into Resilience and Coping Mechanisms - Kei Lairana; Kanawa Wandamar (PELNUS | Pen en Light for Natural Union of Science, 2023)
This research investigates the influence of parental divorce on the emotional development of early adolescents, aiming to provide a comprehensive understanding of immediate and long-term consequences, mediating factors, and coping mechanisms. Employing a mixed-methods approach, the study engages a diverse sample of early adolescents aged 11 to 14 years. Quantitative analyses reveal immediate emotional responses marked by heightened anxiety and sadness, with longitudinal data indicating enduring emotional consequences alongside resilient trajectories. Positive and consistent relationships with custodial parents emerge as significant mediating factors. Gender differences and cultural variations in emotional experiences underscore the importance of tailored interventions. Qualitative insights illuminate diverse coping mechanisms, including engagement in extracurricular activities and the influence of supportive adult figures. The findings hold practical implications for parents, educators, and policymakers, emphasizing the need for positive relationships, open communication, and culturally sensitive support systems. This research serves as a foundation for future inquiries, contributing to a nuanced understanding of the dynamic interplay between parental divorce and the emotional development of early adolescents.